2014
DOI: 10.1039/c3tb21523g
|View full text |Cite
|
Sign up to set email alerts
|

How does iron interact with sporopollenin exine capsules? An X-ray absorption study including microfocus XANES and XRF imaging

Abstract: Sporopollenin exine capsules (SECs) derived from plant spores and pollen grains have been proposed as adsorption, remediation and drug delivery agents. Despite many studies there is scant structural data available. This X-ray absorption investigation represents the first direct structural data on the interaction of metals with SECs and allows elucidation of their structure-property relationships. Fe K-edge XANES and EXAFS data have shown that the iron local environment in SECs (derived from Lycopodium clavatum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 170 publications
(332 reference statements)
2
25
0
Order By: Relevance
“…In recent years, the robust exine capsule, isolated from pollen grains and plant spores, has demonstrated strong potential as a delivery vehicle for the encapsulation of various materials including pharmaceutical drugs, vaccines, contrast agents, and oils . In the materials encapsulation strategies explored thus far, high‐purity exine capsules are required and obtained through vigorous and prolonged processing of pollen grains or spores under harsh conditions using organic solvents, acids and bases at elevated temperatures, or systematic exposure to numerous enzymes .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the robust exine capsule, isolated from pollen grains and plant spores, has demonstrated strong potential as a delivery vehicle for the encapsulation of various materials including pharmaceutical drugs, vaccines, contrast agents, and oils . In the materials encapsulation strategies explored thus far, high‐purity exine capsules are required and obtained through vigorous and prolonged processing of pollen grains or spores under harsh conditions using organic solvents, acids and bases at elevated temperatures, or systematic exposure to numerous enzymes .…”
Section: Methodsmentioning
confidence: 99%
“…These proven therapeutic benefi ts have led to the commercialization of L. clavatum based oral herbal formulations for the treatment of diverse health conditions such as anxiety, albuminuria, constipation, dysentery, gallstones, heartburn, hemorrhoids, impotence, indigestion, irritability, prostatitis, renal colic, and rheumatism. [ 8,[12][13][14][15] The therapeutic activity of these spore constituents is supported by bioassay-guided studies on L. clavatum indicating that a major component, a lycopodine alkaloid, is responsible for the anti-infl ammatory activity of the extract for wound-healing applications. [ 40 ] As other industrial applications, these spores have also been used as a dry powder in latex gloves and condom manufacturing.…”
Section: Macromolecular Encapsulation and Characterization Of Naturalmentioning
confidence: 99%
“…[ 1 ] L. clavatum spores are used in traditional herbal medicine and have been shown to exhibit a wide range of therapeutic benefi ts including improved osteogenesis, [ 11 ] improved cognitive function, [ 12 ] treatment of gastrointestinal disorders, [ 8 ] hepatoprotective activity, [ 13 ] and antioxidative properties. [ 14 ] Recent studies have demonstrated the use of processed L. clavatum shells for encapsulation, [15][16][17][18][19] however, the production of L. clavatum sporopollenin capsules requires the prolonged processing of natural spores with harsh chemical treatments at elevated temperatures, so as to isolate the sporopollenin exine shell. [20][21][22][23][24] In many applications, this extensive processing may be unnecessary and potential therapeutic benefi ts may be lost.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were recorded at 13.5 keV with the incident X-ray beam focused using a pair of Kirkpatrick-Baez mirrors, and a Si (111) double-crystal monochromator. Another "rst" was claimed by Archibald et al 254 who showed how iron interacts with sporopollenin exine capsules. The authors were able to show that foliar applied zinc combined with an organic bio-stimulant increased the mobility of zinc within the sunower.…”
Section: Environmentalmentioning
confidence: 91%